PERANCANGAN KONTROLER PID DAN SLIDING MODE CONTROL UNTUK KESTABILAN HOVER PADA UAV TRIROTOR - Rudy Kurniawan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2014)
Previous research has been done to overcome the problems that occur in UAV Trirotor, one of which is the problem of the control stability . Stability control problems in the presence UAV Trirotor yaw moment caused by torque reaction and the unpaired angle is not accurate in maintaining the stability of the system at the time of the UAV Trirotor hover movement . This paper presents a model of control that can maintain the stability of the system as well as get an accurate tilt angle to solve the UAV Trirotor yaw moment during a hover movement ( hovering) . Control method used is the method of control Proportional Integral Derivative ( PID ) and the Sliding Mode Control ( SMC ). Simulation results show that the PID controller can maintain the stability of the roll angle , pitch angle , yaw angle , and is able to suppress the errors that arise when there is uncertainty in the measurement parameters and the response of the system is able to achieve a given reference . From the results of this control tilt angle values ??obtained on one of the rotor . Then , PID controller and SMC are also able to cope with disturbances and maintain the position of a given height and maintain the robustness of the system.